The wig in the window - Kittscher, Kristen, (Harper, an imprint of HarperCollinsPublishers, 2013)
When their game of neighborhood spying takes a dark turn one night, pre-teen sleuths Sophie Young and Grace Yang find themselves caught in a dangerous cat-and-mouse game with their bizarre guidance counselor, who may be hiding something sinister.